Embryonic soluble human leukocyte antigen-G as a marker of embryo competency in assisted reproductive technology for Chinese women - Guo, Xin-Yu; Jiang, Feng; Cheng, Xue-Jun; Hou, Cai-Ying; Yao, Yuan-Qing (Journal of reproductive medicine, 2013)
To investigate whether embryonic soluble human leukocyte antigen-G (sHLA-G) could be a noninvasive marker for embryo competency in assisted reproductive technology (ART), which is still controversial due to the different detection assays used and the different culture conditions in laboratories. Based on the standardization of IVF procedures and the embryo culture condition, a total of 205 embryo culture supernatants (ESs) from 92 ART cycles were evaluated for sHLA-G contents by chemiluminescent ELISA assay. sHLA-G presence could be detected in 30.7% of the ESs tested. In the cycles where at least one of the embryos transferred was positive for sHLA-G, 51.9% of patients (27/52) achieved a clinical pregnancy. In cycles where none of the embryos transferred secreted detectable amounts of sHLA-G, the pregnancy rate was only 30.0% (12/40, p < 0.05). The implantation rate in sHLA-G-positive cycles was also significantly higher (31.5%) than that in sHLA-G-negative cycles (14.9%, p < 0.05). The results suggested sHLA-G in ESs as a potential marker of embryo competency in ART programs for the Chinese population.